6-5(2x-3)=0

Simple and best practice solution for 6-5(2x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-5(2x-3)=0 equation:


Simplifying
6 + -5(2x + -3) = 0

Reorder the terms:
6 + -5(-3 + 2x) = 0
6 + (-3 * -5 + 2x * -5) = 0
6 + (15 + -10x) = 0

Combine like terms: 6 + 15 = 21
21 + -10x = 0

Solving
21 + -10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -10x = 0 + -21

Combine like terms: 21 + -21 = 0
0 + -10x = 0 + -21
-10x = 0 + -21

Combine like terms: 0 + -21 = -21
-10x = -21

Divide each side by '-10'.
x = 2.1

Simplifying
x = 2.1

See similar equations:

| 8h+7=-1134 | | y=2(x-9)+3 | | 5x-20+x*-3=50 | | 2x+18=-16 | | 1=sin(2piT) | | 294-x=216 | | 10x-x^2=y | | 6x+60=50 | | 200=80-v | | -5=1-5n-n | | -7(-x+4)+10(-x)+3(-4x-2)+34= | | -4(2+1)=-5-2(3) | | 3(4c-1)-3=7c+9 | | Y=-7.5x+11 | | 36m+107-3m=36 | | (x-4)+(2x-7)=0 | | 8m=-3m+1 | | V-2x+3y-z=8 | | 0=-15-3y-4x | | 5p-9=2p+21 | | (X+8)=(4X-28) | | 2.5(2+z)=5(z+2.5) | | y=1.5-1 | | A=6F+4g | | 5x-2(7x-1)=14x | | 4Y^2+x^2=4 | | 3a-2=5 | | 4Y^2+x^2= | | 7(X-5)=71 | | 35x+7=11x+4 | | 4z=6z+2 | | Logx=2.4 |

Equations solver categories